Suppression of collisional loss from a magnetic trap - Arlt, J; Bance, P; Hopkins, S; Martin, J; Webster, S; Wilson, A; Zetie, K; Foot, C (1998)
Caesium atoms in a magnetic trap have a higher loss rate from latin-trap collisions than rubidium under comparable conditions. We have found that this loss from inelastic collisions can be suppressed by periodic optical pumping of the atoms back into the most strongly trapped magnetic state (F = 4, MF = +4), although this reclamation of the strayed atoms gives rise to some heating of the sample. This observation shows that the dominant loss mechanism in the magnetic bias field regime investigated is from collisions which change the magnetic sublevel (quantum number MF) and not the hyperfine level (F quantum number).